The Quality of Managers in Centralized Versus Decentralized Organizations - Sah, R. K.; Stiglitz, J. E. (Quarterly Journal of Economics, 1991)
Raaj K. Sah, Joseph E. Stiglitz; The Quality of Managers in Centralized Versus Decentralized Organizations*, The Quarterly Journal of Economics, Volume 106, Iss